Do education and religiosity affect redistribution preferences? - Mustofa Mustofa; Catur Sugiyanto; Akhmad Akbar Susamto (LPMPP Universitas Negeri Yogyakarta, 2023)
Redistribution preference refers to an individual's tendency or priority in dealing with redistribution problems. This study aims to examine the effects of education and religiosity on redistribution preferences. The novelty in this study is an estimation strategy that includes the influence of education and parental education. The data utilized WVS Wave 7 data. The data analysis used probit regression analysis with a sample of 66,468 respondents. The research results show that the higher the education is, the greater possibility of individual to agree with inequality income will be. Individuals who graduated from elementary and junior high schools tend to agree with equal income, while individuals who graduated from high school and college tend to agree with unequal income. The higher the mother's education is, the greater possibility of individuals to agree with equal income will be. The higher the father's education is, the greater possibility of individuals to agree with unequal income will be. Religiosity has a different influence on redistribution preferences. The obedience variable has a positive influence, while the variable of belief in places of worship and frequency of worship tend to have a negative influence.